What is the Level of Pain in Patients Who Are Inserted Urinary Catheters Using Pure Jelly? - Tria Firza Kumala; Khrisna Wiknusakti; Oop Ropei; Monna Maharani Hidayat; Diwa Agus Sudrajat (STIKep PPNI Jawa Barat, 2022)
Aims: To identify pain level among patients who inserting urine catheter using Pure gel . Design: Used was a description analytic design technique. Methods: This research was conducted using analytic descriptive. Sample collection using purposive sampling technique. This study incorporated a total of 30 participants into the sample pool for analysis. The numerical rating scale is the instrument that is employed. The mean was used to examine the data. Results: The results of total 30 subjects joined in this study, the means rank pain level of patients inserting urine catheter using pure gel was 3.80 (SD 1.186) , with p-value 0.001. There is a difference between the lowest pain level of 0 and the highest pain level of 6 among patients using a pure jelly urinary catheter. Conclusions: The results of this study can describe nursing practice-based evidence in the management of catheter insertion provides the foundation for the development of knowledge in performing urinary catheter insertion actions that can be incorporated into the Standard Operating Procedure (SOP) to help reduce pain in patients who are using urinary catheters.